If it's not what You are looking for type in the equation solver your own equation and let us solve it.
=1-(1-Y)
We move all terms to the left:
-(1-(1-Y))=0
We add all the numbers together, and all the variables
-(1-(-1Y+1))=0
We calculate terms in parentheses: -(1-(-1Y+1)), so:Y=0/-1
1-(-1Y+1)
determiningTheFunctionDomain -(-1Y+1)+1
We get rid of parentheses
1Y-1+1
We add all the numbers together, and all the variables
Y
Back to the equation:
-(Y)
Y=0
| 15.1402/7.3=c | | 6x2+8x-6=0 | | 4x-20+2×+10=180 | | w+3,64=9,76 | | 30/50=9/x | | y-1,7=2,62 | | 270+x=540 | | 3z-50=4z | | M2=13x+3 | | 3/5=c | | 5/3=c | | 3(x+2)=x+2(x=3) | | X+x+6=30 | | 32x-8=7x+2 | | C(x)=0.0001x3-0.09x2+20x+1200 | | 3+5(2x-8)=12 | | 7u+1=4(u-2) | | 4(w+6)=2w+6 | | 3w+21=-8(w-4) | | 3w+21=-8 | | y/8=-1.04 | | y/7.5=23 | | -2x/4+12-4(x-12)=-x/2-4 | | -2r=r/20-5 | | 1/4(4g+10)=33 | | -21r-66=r-572 | | 6z=55 | | -2.3y+5.1=-0.7y+9.9 | | 5x(35+10x)=550 | | 4a=62 | | -29b-45=b+555 | | a-61=2a-21 |